The Effect of Canine Ovariohysterectomy on HSP70 and Anti-HSP70 Antibodies - Yuksel, Murat; Saat, Nevzat; Risvanli, Ali (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
The present study aimed to determine the effects of ovariohysterectomy on blood serum concentrations of Heat Shock Protein (HSP) 70 and anti-HSP70 antibodies in dogs. For this purpose, 87 female stray dogs were used as the materials. Ten milliliters of blood was taken from the animals preoperatively and on the first day postoperatively. The concentration of extracellular HSP70 and anti-HSP70 antibodies in blood serums were measured by using commercial ELISA kits. Subsequently, the preoperatively and postoperatively obtained data were compared. As a result, the mean +/- SD concentration of HSP70 (4.86 +/- 0.99 ng/mL) and anti-HSP70 (109.77 +/- 16.64 ng/mL) antibodies in the dogs' blood samples taken after ovariohysterectomy were found to be significantly lower when compared to the preoperative amounts.
Köpeklerde ovaryohisterektomi'nin HSP70 ve anti-HSP70 antikorları üzerine etkisi
Keywords: HSP70; Anti-HSP70; Ovariohysterectomy; Dog